صعوبات النحو العربي من وجهات نظر دارسي اللغة العربية في الجامعة الإسلامية العالمية بماليزيا - Siti Mariyam binti Kamarudin (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study aims to study the difficulty factors in learning Arabic grammar among students in International Islamic University Malaysia. The difficulties focus on grammar topics, books, teachers and students. The researcher relied on qualitative approach to get the desired information. The selected type of interview was semi-structured. The researcher conducted interviews with six students from International Islamic University Malaysia. Participants consisted of four female students and two male students who were from Arabic Language and Literature Department. The results show that these four factors did affect the learning of Arabic grammar and it made it difficult to learn Arabic grammar. The most difficult topics were: prepositions, additions, adverbs, and conjunctions. Students found the textbook difficult because of grammatical terms, language used by the author, complex explanations, disorganized presentation of contents, and difference opinions among scholars. The results show that the views of students were totally different from their teachers' views which are led to dissatisfaction among students. The most important factors that contributed in these difficulties was students themselves who are not native speakers of Arabic. Result also show that some of the factors linked to other factors such as student factor linked to teacher factor and also the book factor.